(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
The objective of the present investigation was to design mucoadhesive microspheres to achieve a substantial increase in length of stay of the drug in the GI tract of glipizide for treatment of type 2 diabetes mellitus. Glipizide is a second-generation sulfonylurea derivative used for the treatment of type II diabetes. Its short biological half-life (0.3 ± 0.7 h) necessitates the need to be administered in two or three doses of 2.5-10 mg per day. Mucoadhesive microsphere exhibit a prolonged residence time at the site of application and facilitate an intimate contact with the underlying absorption surface and thus contribute to improved or better therapeutic performance of drug. It would, therefore be advantageous to have means for providing an intimate contact of the drug delivery system with the absorbing membranes. In the present study, alginate based mucoadhesive microspheres of were prepared by ionotropic external gelation technique utilizing calcium chloride (CaCl2) as a cross linking agent, to take the advantage of swelling and mucoadhesive property of alginate beads for improving the oral delivery of glipizide. Interaction studies performed using FTIR spectroscopy and DSC revealed that there was no drug to polymer interactions. The prepared microspheres are discrete, spherical and free flowing which was characterized by entrapment efficiency, particle size, micromeritic properties, in-vitro release behavior, scanning electron microscopy (SEM), in-vitro wash off test etc. Depending upon the variability in the concentration of sodium alginate, time of cross linking agent, the factors like particle size, and incorporation efficiency and release rate and mucoadhesion properties of microspheres varies. It was observed that increasing the polymer concentration along with the cross-linking time given the better affect on microspheres characteristic and percentage release of drug. Formulation F8 containing 5% w/v sodium alginate was selected as best formulation by considering its better % drug entrapment [84.31%] and flow properties [Carr’s index (8.204), angle of repose (31.15)].